Effects of ACE inhibition and β-receptor blockade on energy metabolism in rats postmyocardial infarction - Hügel, S; Horn, M; De Groot, M; Remkes, H; Dienesch, C; Hu, K; Ertl, G; Neubauer, S (1999)
Chronic treatment with β-receptor blockers or angiotensin-converting enzyme (ACE) inhibitors in heart failure can reduce mortality and improve left ventricular function, but the mechanisms involved in their beneficial action remain to be fully defined. Our hypothesis was that these agents prevent the derangement of cardiac energy metabolism. Rats were subjected to myocardial infarction (MI) or sham operation. Thereafter, animals were treated with bisoprolol, captopril, or remained untreated. Two months later, cardiac function was measured in the isolated heart by a left ventricular balloon (pressure-volume curves), and energy metabolism of residual intact myocardium was analyzed in terms of total and isoenzyme creatine kinase (CK) activity, steady-state levels (ATP, phosphocreatine), and turnover rates (CK reaction velocity) of high-energy phosphates (31P nuclear magnetic resonance) and total creatine content (HPLC). Bisoprolol and partially captopril prevented post-MI hypertrophy and partially prevented left ventricular contractile dysfunction. Residual intact failing myocardium in untreated, infarcted hearts showed a 25% decrease of the total, a 26% decrease of MM-, and a 37% decrease of the mitochondrial CK activity. Total creatine was reduced by 15%, phosphocreatine by 21%, and CK reaction velocity by 41%. Treatment with bisoprolol or captopril largely prevented all of these changes in infarcted hearts. Thus the favorable functional effects of β- receptor blockers and ACE inhibitors post-MI are accompanied by substantial beneficial effects on cardiac energy metabolism.